PENGELOLAAN SAMPAH ORGANIK MENJADI PUPUK KOMPOS - Wahyu Adia Ningrum; Husnul Khatimah; Purnama Putra (An-Nizam, 2022)
Along with population density, waste is one of the crucial issues that is still being debated. This can be seen in one of the cities in Indonesia, namely Bekasi City, which is one of the cities that accommodates a lot of urbanization. The increase which increases by almost 2.5% every year is a crucial problem for the people of Bekasi City, especially plastic waste that is difficult to destroy. Garbage will accumulate more and more due to the lack of public understanding about sorting in waste management. By educating and socializing to the public about the importance of good and correct waste management, people will realize that waste is not a trivial problem and will make the surrounding environment uncomfortable. The impact generated after socializing, the community will be able to sort waste to reduce the negative impact of domestic waste, make the surrounding environment clean and comfortable, and increase public awareness to maintain cleanliness. Therefore, the community must increase awareness of the importance of carrying out 3R efforts, namely Reuse; Reduce; and Recycle.